KAJIAN KERENTANAN KAWASAN PESISIR TERHADAP BENCANA KENAIKAN MUKA AIR LAUT (SEA LEVEL RISE) DI INDONESIA - Nabila Afifah Azuga (Universitas Hang Tuah, 2021)
Coastal area is defined as a transitional area between land ecosystems and marine ecosystems. Coastal areas are very vulnerable to environmental pressures, both on land and at sea. One form of pressure that threatens the sustainability of coastal areas almost all over the world is the phenomenon of sea level rise. The phenomenon of sea level rise itself is a result of the expansion and contribution of ice due to increased of melting ice as a result of global warming. It is predicted that in 2100 there will be a rise of sea level that reach 0.26 to 0.98 meters. Sea level rise can be analyzed using a trendline based on monthly slopes to determine the average of sea level rise per year. In addition, to determine the vulnerability of coastal areas to sea level rise, it can be determined through two aspects: aspects of geophysical vulnerability and aspects of socio-economic vulnerability.